GeneXpert MTB/RIF in diagnosis of tuberculous meningitis (TBM) in paediatric patients at a tertiary care children’s hospital in Pakistan over a period of 4 years - Majeed, Nadia; Mehdi, Naima; Tahir, Anum; Aroob, Iqra; Omer, Shameeqa; Ali, Farwa (Journal of the Pakistan Medical Association, 2025)
The current study was planned to report the frequency of tuberculosis meningitis in the paediatric population of Pakistan using the GeneXpert Mycobacterium tuberculosis/Rifampicin (MTB/RIF) assay. Data of 569 cerebrospinal fluid samples collected between October 2019 and October 2023 at a tertiary care children’s hospital was retrospectively analysed. Mycobacterium tuberculosis was detected in 101(17.7%) samples, with 57(56%) of them being from male patients. The highest tuberculous meningitis incidence 55(54.5%) was found in children aged 0-4 years, while those aged 10-14 years showed the lowest incidence 13(12.9%). Rifampicin resistance was present in 3(2.9%) cases. The findings highlighted the importance of incorporating GeneXpert MTB/RIF testing in clinical evaluation for suspected tuberculous meningitis cases in paediatric patients. Key Words: Tuberculosis meningitis, GeneXpert MTB/RIF assay, Rifampicin resistance, Paediatric TBM, Mycobacterium tuberculosis.